2015
DOI: 10.1186/s13019-015-0265-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcome analysis after surgical management of ventricular septal rupture complicating acute myocardial infarction: a retrospective analysis

Abstract: BackgroundVentricular septal rupture (VSR) is an uncommon but well-recognized mechanical complication of acute myocardial infarction (AMI). The outcome of VSR remains poor even in the era of reperfusion therapy. We reviewed our experience with surgical repair of post-infarction VSR and analyzed outcomes in an attempt to identify prognostic factors.MethodsFrom October 1995 to December 2013, data from 47 consecutive patients (mean age, 68 ± 9.5 years) with post-infarction VSR who underwent surgical repair at our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 27 publications
2
42
2
1
Order By: Relevance
“…Our experience suggests that V‐A ECMO successfully stabilizes patients with VSR and refractory CS ( Table ) who would not definitely be considered suitable candidates for surgical repair. Similar outcomes have recently been reported by other groups . Therefore, we suggest early V‐A ECMO initiation to be considered as a reasonable approach in patients who are haemodynamically unstable before contemplated surgery.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our experience suggests that V‐A ECMO successfully stabilizes patients with VSR and refractory CS ( Table ) who would not definitely be considered suitable candidates for surgical repair. Similar outcomes have recently been reported by other groups . Therefore, we suggest early V‐A ECMO initiation to be considered as a reasonable approach in patients who are haemodynamically unstable before contemplated surgery.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, published literature on this topic is limited to a small number of case reports and case series . Furthermore, different timing and choice of therapy in each case does not allow any meaningful analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tang et al [18] and Yalcinkaya et al [19] also revealed a similar incidence of risk factors. On the other hand, other studies showed that in addition to hypertension, the incidence of diabetes was often as high as 44.7% and in another study 65.5% [20,21]. With reference to the group we analyzed (13; 25%), their results are very high.…”
Section: Occurrence Of Patients' Risk Factors For Mechanical Complicamentioning
confidence: 70%
“…Post-MI VSD is often presented with total left anterior descending artery (LAD) occlusion; it mostly occurs at anterolateral localization and less often at posterior localization after inferior MI (2) . A 55 year old male patient came to the emergency room with chest pain.…”
mentioning
confidence: 99%